Asystole during pulmonary artery catheter insertion under general anesthesia - Chaudhuri, Swapna (Medknow Publications & Media Pvt Ltd, 2012)
In spite of ongoing debate for the past 40 years, pulmonary artery catheters remain in use for invasive hemodynamic monitoring and management of critically ill patients. We describe a case of a sudden onset of asystolic cardiac arrest during the placement of a pulmonary artery catheter, while under general anesthesia. A brief review of the literature highlighting arrhythmic complications associated with pulmonary artery catheterization is also presented.